Preparation of Novel Thermoplastic Elastomers by Graft Copolymerization using Metallocene Catalyst and Cocatalyst System - Kim, Min Seong; Kim, Jung Soo; Kim, Jin Hoon; Chang, Young-Wook; Kim, Dong Hyun (Asian Journal of Chemistry, 2016)
Poly(ethylene-ter-1-decene-ter-divinylbenzene) (PEDV) is prepared using rac-Et(Ind)2ZrCl2 and dimethylanilinium tetrakis-(pentafluorophenyl)borate/triisobutylaluminum as a metallocene catalyst and a cocatalyst system, respectively. The characteristic changes of the terpolymerization product according to the varying concentration of comonomers such as 1-decene and divinylbenzene (DVB) were also studied. The structure of poly(ethylene-ter-1-decene-ter-divinylbenzene) was determined by 1H NMR and the catalytic activity of the terpolymerization was found to be over 14000 kg/mol·h. PEDV-g-poly(styrenic monomers) were prepared using various styrenic monomers such as styrene, tert-butylstyrene, a-methylstyrene and p-methylstyrene. The structure of these graft copolymers was also elucidated by 1H NMR. The differential scanning calorimetry confirmed that the prepared graft copolymers had two glass transition temperatures and a high melting temperature range (250-309 °C).